PROGRAM FOR THE DEVELOPMENT OF THE MOTIVATIONAL AND VOLITIONAL SPHERE OF MILITARY PERSONNEL OF THE NATIONAL GUARD OF UKRAINE - Yurieva, Nataliia; Lyman, Anastasiia (Honor and Law, 2022)
The article identifies the relevance of the development of the motivational and volitional sphereof military personnel of the National Guard of Ukraine. It is determined that the general structure of the motivational and volitional sphere of military personnel of the National Guard of Ukraine consists of the following components: interest in military service, the presence of understanding to effectively perform professional tasks, the desire to succeed in the professional field of the military, the desire for self-development, self-improvement and self-realization, a sense of duty and responsibility to the Motherland.To form the components of the motivational and volitional sphere of military personnel of the National Guard of Ukraine, it is expedient to use psycho-training programs. The content of the training is focused on improving the defined structure of the motivational-free sphere of military personnel of the National Guard of Ukraine, which will promote the ability to maintain the effectiveness of military service, its self-realization and self-improvement in the profession, self-education and teamwork.Socio-psychological training «Development of motivation of military personnel of the National Guard of Ukraine» is developed for servicemen-officers and servicemen of military service under the contract. Conducting training sessions is designed for 5 days and 6 hours, each day logically continues each other. Due to this, the participants gradually delve in to the process of realizing their motivational features (control of personal experiences, adjustment of goals, planning, methods of self-regulation, etc.). Homework and keeping a psychological diary help to consolidate the material.The general results of approbation of training and prospects of its further use for increase of efficiency of service and combat activity of military personnel are given. The effectiveness of the training is ensured by a number of common opportunities, which include: receiving feedback, supporting people who have common tasks, problems, experiences that arise during classes, and so on.